CALL-Mediated task-based language teaching: A speaking project with online audience in Indonesia - Oktavia Widiastuti; Fransisca Maria Ivone; Teguh Sulistyo; Didik Hartono; Emy Sudarwati; Santi Prastiyowati (Indonesian Journal of Applied Linguistics, 2022)
Tasks and technology are reciprocally related since the integration of technology can benefit task-based language teaching (TBLT) implementation. This study investigates students’ speaking performance, learning experiences, and perceptions in a speaking course specially designed with video recording activities involving online audiences based on the principles of TBLT. Thirty-eight undergraduate students majoring in English and enrolled in the speaking class served as the respondents. The data were collected through speaking tests, Likert scale questionnaires, and interviews. The findings indicated that the students developed their speaking performance after experiencing speaking class through a computer-assisted language learning (CALL)-mediated TBLT with video recording activities. They were also able to find their strengths and weaknesses by watching their own video recordings on YouTube. The findings also showed that the students had positive learning experiences and perceptions of video recording activities with online audiences on YouTube. Nevertheless, a further investigation of the online interactions toward the use of tasks and digital learning platforms with online audiences is highly advised.